The Kingdom of Bhutan - Karim Quintino (Political Observer, 2019)
Most democratic transitions have demonstrated how it is possible to move from an authoritarian starting point towards an ongoing state of compromise. The Kingdom of Bhutan, a small state bordering India and China and located deep within the Himalayan Mountains, stands as an illustrative case of that paradigm. Not only has that country recently welcomed extensive democratic practices after a century of monarchical rule, but more interestingly, it did so by royal decree. This unusual top-down transition saw the ruling monarch effectively “enforcing” democracy onto the people rather than the opposite, which defied the customary paradigm of democratisation. Nonetheless, Bhutan’s process of democratisation has been hampered at an initial stage because most Bhutanese citizens remained satisfied with the previous monarchical regime. As such, the purpose of the communication is to enlighten the reader with the features of Bhutanese democracy and its preceding process of democratisation, while providing a possible answer on whether there is a common pattern in the transitional process of authoritarianism to democracy. In order to do so, the article firstly looks at Bhutan’s modern political history; secondly, it analyses the idiosyncrasies of Bhutanese democracy; and thirdly, it shows how the historical, religious and social background of Bhutan has led to a peculiar process of democratic consolidation.